M-SAKHI - Mobile health solutions to help community providers promote maternal and infant nutrition and health: a description of development of the Program Impact Pathway using Theory of Change - Archana B Patel; Priyanka N Kuhite; Samreen Sadaf Khan; Amrita Puranik; Ashraful Alam; Michael J Dibley (Cambridge University Press, 2024)
Abstract Objective: Behaviour Change Communication (BCC) intervention programmes often lack documentation of successful processes. This manuscript aims to describe the development of Program Impact Pathway (PIP) using Theory of Change (ToC) approach for a mHealth BCC intervention titled 'Mobile Solutions Aiding Knowledge for Health Improvement (M-SAKHI)' aimed at reducing stunting in infants at 18 months of age. Design: The PIP was developed using ToC to design the intervention and plan its implementation. Literature review and data from previous pilots helped to identify health service gaps that needed to be addressed by the PIP of this intervention. Setting: M-SAKHI was implemented in 244 villages under governance of forty primary health centres of Nagpur and Bhandara districts of eastern Maharashtra in central India. Participants: The study investigators and the public health stakeholders participated in developing the PIP. M-SAKHI evaluation study recruited 2501 pregnant women who were followed up through delivery until their infants were 18 months old. Results: The PIP was developed, and it identified the following pathways for the final impact: (1) improving maternal and infant nutrition, (2) early recognition of maternal and infant danger signs, (3) improving access and utilisation to healthcare services, (4) improving hygiene, sanitation and immunisation practices, and (5) improving implementation and service delivery of community health workers through their training, monitoring and supervision in real time. Conclusion: This paper will illustrate the significance of development of PIP for M-SAKHI. It can aid other community-based programmes to design their PIP for nutrition-based BCC interventions.